Scrub typhus in India: Whether increased reporting or expanding geographies? - Kumar, Chandra Mohan; Sharma, Preeti; Patwari, A K (Indian Journal of Child Health, 2016)
Scrub typhus is a potentially fatal disease with serious complications in untreated cases or where there is delay in starting treatment. It has been considered to be limited to certain geographic areas with vegetations and cattle grazing fields like Jammu. Scrub typhus cases/outbreaks have been reported in the recent past from South India, Mumbai, Goa, Himachal Pradesh, and Haryana. Recently, we had a case of scrub typhus in a child residing in Delhi with no history of travel outside. A 10-year-old girl admitted with high-grade fever, abdominal pain, myalgia, and erythematous rash with hepatomegaly but without lymphadenopathy and developed splenomegaly in the 2nd week of illness. She was confirmed to be a case of scrub typhus after immunoglobulin M enzyme-linked immunosorbent assay for the disease. Scrub typhus is a matter of great public health importance that all medical practitioners should be sensitized about this disease and its varying presentations and complications.